Glycyrrhizic acid attenuates growth of Leishmania donovani by depleting ergosterol levels - Dinesh, Neeradi (Exp Parasitol, 2017)
In the present study, glycyrrhizic acid (GA) the main component of Glycyrrhiza glabra was evaluated for its efficacy as antileishmanial agent and its mode of action explored. GA inhibits promastigotes and intracellular amastigotes in a dose dependent manner at an IC(50) value of 34 ± 3.0 μM and 20 ± 4.2 μM respectively. GA was non-toxic against THP-1 macrophage host cell line. GA was found to inhibit recombinant Leishmania donovani HMG-CoA reductase (LdHMGR) enzyme at the half-maximum inhibitory concentration of 24 ± 4.3 μM indicating the sensitivity and specificity of GA towards the enzyme. However, GA could cause only 30% reduction in HMGR activity when measured in Leishmania promastigotes treated with 34 μM of GA. Interestingly western blot analysis revealed fivefold reduced HMGR expression in GLA treated promastigotes. To further study the mode of action of GA, we used transgenic parasites overexpressing LdHMGR. Results indicated that ∼2 fold resistance was exhibited by LdHMGR overexpressing promastigotes to GA with an IC(50) value of 74 μM compared to the wild type parasite. This explained the specific binding of GA to LdHMGR enzyme. There was ∼2 fold depletion in ergosterol levels in wild type promastigotes compared to the HMGR overexpressors. This data was further validated by exogenous supplementation of GA treated cells with ergosterol and 40% reversal of growth inhibition was observed. The results obtained suggested that GA kills the parasite by affecting sterol biosynthetic pathway, especially by inhibiting the L. donovani HMGR and altering ergosterol levels. The finding from the current study shows that GA is a potential antileishmanial chemotherapeutic agent.